Effects of Osmolyte Precursors on the Distribution of Compatible Solutes in Methanohalophilus portucalensis - Robinson, P. M. (1997)
The halophilic methanogen Methanohalophilus portucalensis synthesizes three distinct zwitterions, (beta)-glutamine, N(sup(epsilon))-acetyl-(beta)-lysine (NA(beta)Lys), and glycine betaine, as osmolytes when it is grown at high concentrations of external NaCl. The selective distribution of these three species was determined by growing cells in the presence of osmolyte biosynthetic precursors. Glycine betaine is formed by the stepwise methylation of glycine. Exogenous glycine (10 mM) and sarcosine (10 mM), although internalized, do not bias the cells to accumulate any more betaine. However, exogenous N,N-dimethylglycine (10 mM) is available to the appropriate methyltransferase and the betaine generated from it suppresses the synthesis of other osmolytes. Precursors of the two zwitterionic (beta)-amino acids ((beta)-glutamate for (beta)-glutamine and (alpha)-lysine and diaminopimelate for NA(beta)Lys) have only small effects on (beta)-amino acid accumulation. The largest effect is provided by L-(alpha)-glutamine, suggesting that nitrogen assimilation is a key factor in osmolyte distribution.